Lymphocyte Subpopulations in Sheehan's Syndrome - Atmaca, Hulusi; Arasli, Mehmet; Yazici, Zihni Acar; Armutcu, Ferah; Tekin, Ishak Ozel (Springer, 2013)
The role of autoimmunity in the development of Sheehan's syndrome is obscure. There are a limited number of studies investigating the immunological alterations accompanying Sheehan's Syndrome. Our objective was to evaluate lymphocyte subsets in these patients. We conducted a cross-sectional clinical study. Cytofluorometry was used for the immunophenotyping of peripheral blood leukocytes from patients with Sheehan's syndrome followed up in the endocrine clinic during 2005-2009. Fifteen consecutive patients (mean age 61.6 +/- A 11.3, range 34-75 years) and 25 healthy controls (mean age 56.7 +/- A 10.6, range 34-80 years) were included. There was no statistically significant difference between the groups in terms of mean age. The percentages of CD19(+), CD16(+)/56(+), CD8(+)28(-), gamma delta TCR+, CD8(+); the total lymphocyte counts; and the ratio of CD8(+)28(-)/CD8(+)28(+) were similar (p > 0.05) between patients and controls. Whereas the leucocyte counts (p = 0.003), the percentage of CD3 (+) DR (+) (p < 0.001), CD8(+)28(+) (p = 0.030), CD4(+)CD25(+) (p = 0.007), the ratio of CD3 (+) DR+/CD3 (p < 0.001) were higher; the percentage of CD3 (p = 0.020), CD4 (p < 0.001) and the ratio of CD4/CD8 (p = 0.006) were lower in patients with Sheehan's syndrome compared to healthy controls. There was a positive correlation between the duration of illness and the percentage of CD3(+)DR(+) (r = 0.53, p = 0.03) expression. Some peripheral lymphocyte cell subsets show marked variation in patients with Sheehan's syndrome in comparison to matched healthy subjects, which may have implications for altered immune regulation in these patients. High CD3 (+) DR (+) expression that correlates with the duration of illness in Sheehan's patients is suggestive of an ongoing inflammation accompanying the slow progression of pituitary dysfunction in Sheehan's syndrome. It is not clear if these cellular alterations contribute to the cause or consequence of pituitary deficiency in Sheehan's syndrome.
Keywords: Sheehan's Syndrome; Lymphocyte Subsets; Regulatory T Cells; Suppressor T Cells; Cytotoxic T Cells